Pancreatic metastases from ovarian carcinoma—diagnosis by endoscopic ultrasound-guided fine needle aspiration - Hasmoni, Mohamed Hadzri; Che Sayuti, Suzila; George, Abraham Matthew; Salleh, Rosemi (Blackwell Publishing Asia Pty Ltd, 2010)
Pancreatic metastases are very uncommon and originate most commonly from lung, colon, breast and kidney. Ovarian adenocarcinoma has been reported as a primary site of pancreatic metastasis, but diagnosing using EUS-FNA is rarely being reported. Case report We reported a case of multiple metastases to the pancreas from ovarian carcinoma occurred 3 years after original resection of the primary tumour. A 60 year-old lady with prior history of stage IIIC ovarian carcinoma was referred to the Gastroenterology Unit for the evaluation of multiple pancreatic mass. She was diagnosed with the malignancy 3 years earlier and had undergone total abdominal hysterectomy and bilateral salphingo-oophorectomy. She presented with severe epigastric pain associated with nausea and mass per abdomen. She was treated as acute pancreatitis based on clinical and biochemical results. Initial trans-abdominal ultrasound showed multiple pseudocyst within the pancreas, with the largest measuring 4.7 × 3.6 cm. Similar fi ndings were noted from CT scan of the abdomen. EUS revealed multiple cystic lesions with heterogenous appearance at the head and body of the pancreas. Endoscopic ultrasound guided fi ne needle aspiration (EUS-FNA) was performed and the result showed pancreatic papillary adenocarcinoma which was morphologically identical to the surgical specimen of her ovarian mass. She was then treated with palliative chemotherapy. Conclusion EUS-FNA in conjunction with immunohistochemistry is a useful tool for diagnosing pancreatic lesion and mass. Although pancreatic metastases are rare, we still need to exclude the diagnosis for any pancreatic lesion.